The Role of Brand Image as a Mediator of Digital Promotion and Electronic Word of Mouth on Purchase Decisions - Fellyza Farah Audina; Haunan Damar; Hertiana Ikasari; Suhita Whini Setyahuni (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2026)
Background: Employing brand image as an intermediary variable, this research seeks to assess the influence exerted by digital promotion and electronic word-of-mouth (e-WOM) on purchase decisions at ZAP Clinic Semarang. Objectives: The present research analyzes both the unmediated impacts of digital promotion and electronic word-of-mouth (e-WOM) on brand image and purchase decisions at ZAP Clinic Semarang, as well as the extent to which brand image serves as an intermediary in the linkage between those marketing tactics and subsequent consumer purchasing behavior. Methodology: The research employed a quantitative framework based on a survey technique. Purposive sampling yielded 100 respondents meeting the following inclusion criteria: previous use of ZAP Clinic Semarang’s services, receipt of digital promotional stimuli, interaction with online consumer reviews, age of at least 17 years, and domicile within Semarang City. Analytical procedures were carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) as executed in SmartPLS 4.0. Findings: Although digital promotion exhibits no statistically significant direct effect on purchase decisions, electronic word of mouth (e-WOM) demonstrates a positive and statistically significant impact on both brand image and consumer purchasing behavior. Furthermore, the findings confirm that brand image serves as a significant mediating mechanism in the relationship between digital marketing strategies, particularly e-WOM, and purchase decisions. Conclusions: Purchase decisions for aesthetic clinic services are more driven by consumer experience and online recommendations through e-WOM, as well as positive perceptions of brand image, compared to digital promotion alone. Digital promotion may be ineffective unless it first enhances brand image.